"Excessos de patriotismo" : terrorismo de estado e os Grupos de Onze Companheiros no Rio Grande do Sul - 1964/1965 - Almeida, Marli de (2018)
This thesis has as its central object the Groups of Eleven Companions or Nationalist Commands, organized by Leonel Brizola from October 1963 onwards for the "defense of the democratic achievements of the Brazilian people, for the immediate reforms and for the national liberation." There was extraordinary adherence to the movement, especially in Rio Grande do Sul, demonstrating the desire for popular participation and political engagement at the moment, as well as an expectation of changes through the realization of basic reforms, especially agrarian reform. In the context of the Cold War, this mobilization was seen and vaunted as a subversion and advance of the revolutionary war that would establish communism in Brazil. The formation of these groups provided the conservative groups, who feared the leftist expansion and the popular mobilization, already conspired for the deposition of João Goulart of the presidency. With the civil-military coup of March 31, 1964, a dictatorial government was established which, in order to eliminate all opposition to the regime, used State terrorist practices (TDE), directly affecting people who participated in the Groups of Eleven or who were suspected of being involved in such mobilization. The main source for this study are the lawsuit claims for political persecution, made possible by Law 11.042 of November 18, 1997, whereby the State of Rio Grande do Sul “assumed responsibility for physical and psychological damages caused to persons detained for political reasons and established norms to be indemnified”, made available for public consultation in the Public Archive of the State of Rio Grande do Sul. For the purpose of this research, 440 cases were selected, in which the claimants allege imprisonment, persecution and/or torture for involvement with the Nationalist Commands or are cited in other proceedings as members of such groups. By analyzing these processes, the aim is to establish a profile of those involved with the groups, the motivations for their adherence to the movement, the places where there was a greater formation of the groups, the extent of the repression that was still unleashed in 1964 and the effects of state violence on life the persecuted politicians and those of their families.